2016
DOI: 10.1002/anie.201609853
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Chiral Aminocyclopropanes by Rare‐Earth‐Metal‐Catalyzed Cyclopropene Hydroamination

Abstract: The search for efficient and selective routes for the synthesis of chiral aminocyclopropane derivatives is of great interest and importance as these structures are important components of biologically active natural products and pharmaceuticals. We herein report the enantioselective intermolecular hydroamination of substituted cyclopropenes with various amines catalyzed by chiral half-sandwich rare-earth-metal complexes. This method constitutes a 100 % atom-efficient route for the synthesis of a variety of chi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
54
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 131 publications
(55 citation statements)
references
References 62 publications
(20 reference statements)
0
54
0
1
Order By: Relevance
“…First, we examined the reaction of 2,6‐lutidine ( 1 a ) with 3‐methyl‐3‐phenylcyclopropene ( 2 a ) as a model reaction with yttrium complex Ph‐Y as the catalyst. The neutral complex Ph‐Y alone was not effective for the C−H addition of 1 a to 2 a (Table , entry 1), although it had shown excellent activity and enantioselectivity in the hydroamination of cyclopropenes with amines . In the presence of [Ph 3 C][B(C 6 F 5 ) 4 ] as a cocatalyst, Ph‐Y showed moderate activity for the C(sp 3 )−H addition of 1 a to 2 a , affording the desired product 3 a in 76 % yield at room temperature in 48 h, albeit with poor stereoselectivity (1.1:1 d.r.…”
Section: Methodsmentioning
confidence: 78%
See 1 more Smart Citation
“…First, we examined the reaction of 2,6‐lutidine ( 1 a ) with 3‐methyl‐3‐phenylcyclopropene ( 2 a ) as a model reaction with yttrium complex Ph‐Y as the catalyst. The neutral complex Ph‐Y alone was not effective for the C−H addition of 1 a to 2 a (Table , entry 1), although it had shown excellent activity and enantioselectivity in the hydroamination of cyclopropenes with amines . In the presence of [Ph 3 C][B(C 6 F 5 ) 4 ] as a cocatalyst, Ph‐Y showed moderate activity for the C(sp 3 )−H addition of 1 a to 2 a , affording the desired product 3 a in 76 % yield at room temperature in 48 h, albeit with poor stereoselectivity (1.1:1 d.r.…”
Section: Methodsmentioning
confidence: 78%
“…We have recently found that half‐sandwich rare‐earth alkyl complexes can serve as efficient catalysts for the C−H addition of heteroatom‐containing aromatic compounds, such as anisoles, pyridines, and N , N ‐dimethylanilines, to various alkenes . By using some chiral half‐sandwich rare‐earth catalysts, we have also achieved the enantioselective C(sp 2 )−H addition of pyridines to 1‐alkenes and the enantioselective intermolecular hydroamination of cyclopropenes with amines . These results encouraged us to examine whether chiral half‐sandwich rare‐earth catalysts could be employed for the asymmetric C−H addition of pyridines to cyclopropenes.…”
Section: Methodsmentioning
confidence: 99%
“…In 2016, Hou et al reported the first enantioselective intermolecular hydroamination of cyclopropenes with various amines by using chiral half-sandwich catalysts based on samarium, yttrium and lanthanum (Scheme 8) [17].…”
Section: Group 3 / Rare-earth Catalysts -Lanthanidesmentioning
confidence: 99%
“…6 Recently, the Hou lab disclosed the first highly enantioselective intermolecular hydroaminations with aliphatic amines, where chiral lanthanide half-sandwich catalysts allow for stereoselective amine additions to cyclopropenes. 7–10 In this work, we report the enantioselective 1,2-addition of alkyl amines to unsymmetrical acyclic dienes 11–13 catalyzed by a cationic Pd–PHOX complex. 14 Transformations afford allylic amines 15 in up to 91% yield in 3–24 h without added Brønsted acid.…”
mentioning
confidence: 99%